Equity financing activities and European value-growth returns - Walkshäusl, Christian (Journal of Banking & Finance, 2015)
This paper extends the U.S. evidence in Bali et al. (2010) to European stock markets. Like in the United States, European value-growth returns are strongly dependent on the valuation signals contained in the firm’s equity financing activities. The high returns of value firms are due to value purchasers, while the low returns of growth firms are due to growth issuers. Among value issuers and growth purchasers, there exists no value premium at all. The large return difference between value purchasers and growth issuers cannot be explained by common risk factors. However, employing Piotroski and So’s (2012) recently proposed market expectation errors approach shows that the observed value-growth returns can be attributed to mispricing.